Effects of Tillage Treatments on Weed Control in a Maize Field on Sandy Loam Soil of North Eastern Nigeria - Kawuyo, U. A.; Haque, M. A.; Usman, A. M. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2007)
This study was carried out to determine the effects of tillage treatments; namely: zero-tillage (T1), disc ploughing (T2), disc harrowing (T3) and disc ploughing followed by disc harrowing (T4) on weed control in a maize field. Plant height (cm), weed density (No/m2) and fresh weed weight i.e. weed biomass (g/m2) were measured at various growth stages of the crop, while grain yield (Kg/ha) was determined after harvest. The study was conducted in 1999 and 2000 farming seasons. The results showed that there were significant differences between tillage treatments for all the measured parameters in both years. The grain yield increased by 34and 36% for the year 1999 and 2000 respectively when treatments T1 and T4 were compared. A reduction in weed density at harvest by 57 and 52% in 1999 and 2000 respectively was obtained when treatments T1 and T4 were compared. Also, there was a 53 and 34% reduction in 1999 and 2000 respectively for the weed biomass when these two treatments were compared. It was recommended that treatment T4 be adapted for better weed control